Implementasi Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Personil Melalui Disiplin Kerja Pada Satuan Korps Brigadir Mobil Polisi Republik Indonesia - Fadli Ramadhan; Zaharuddin; Gada Sembada; Eddy Hermawan Hasudungan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of leadership style implementation on work discipline as a moderating variable, to examine the effect of work motivation on work discipline as a moderating variable, to analyze the influence of leadership style and work motivation on personnel performance, and to assess work discipline as a moderating variable affecting personnel performance in the Mobile Brigade Corps Unit of the Indonesian National Police. This research uses a quantitative approach. The population studied consists of 1,327 Mobile Brigade personnel in the Mobile Brigade Corps Unit, Kelapa Dua, Depok, West Java. The sampling technique used is Probability Sampling with the Simple Random Sampling method. The sample size was calculated using the Slovin formula, resulting in 95 respondents. Data collection techniques employed in this study include questionnaire distribution and observation. The data analysis technique used is the SPSS version 20 program.The results of the study show that: (1) There is no significant influence of the Leadership Style variable (X1) on Work Discipline (M) in the Mobile Brigade Corps Unit of the Indonesian National Police. This is evidenced by a path coefficient of 0.076 with a t-count value of 1.982 and a t-table value of 1.985, where 1.982 < 1.985 with a probability of 0.050. (2) There is a significant influence of the Work Motivation variable (X2) on Work Discipline (M) in the Mobile Brigade Corps Unit of the Indonesian National Police. This is proven by a path coefficient of 0.908 with a t-count value of 23.736 and a t-table value of 1.985, where 23.736 > 1.985 with a probability of 0.000 (0.000 < 0.05). (3) There is a significant influence of the Leadership Style (X1) and Work Motivation (X2) variables on Personnel Performance (Y) in the Mobile Brigade Corps Unit of the Indonesian National Police. This is demonstrated by an F-count value of 48.095 and an F-table value of 2.70, where 48.095 > 2.70 with a probability of 0.000 (0.000 < 0.05). (4) There is a significant influence of the Work Discipline variable (M) on Personnel Performance (Y) in the Mobile Brigade Corps Unit of the Indonesian National Police. This is indicated by a path coefficient of 0.982 with a t-count value of 4.779 and a t-table value of 1.985, where 4.779 > 1.985 with a probability of 0.000 (0.000 < 0.05).